CONDITIONAL DEATH PENALTY POLICY UNDER LAW NUMBER 1 OF 2023 ON THE CRIMINAL CODE: A LEGAL CERTAINTY PERSPECTIVE - Putri, Amiratul Mardhiyah; HZ, Evi Deliana; Ardiyanto, Syaifullah Yophi (Jurnal Ilmiah Advokasi, 2025)
The conditional death penalty, as regulated in Article 100 of Law Number 1 of 2023 concerning the Criminal Code, reflects a shift toward a more humanistic and rehabilitative approach to capital punishment in Indonesia. This policy aims not only to provide convicts with an opportunity for reform but also to minimize the risk of wrongful execution and accommodate divergent public opinions on the death penalty. This study employs normative legal research with a focus on the principle of legal certainty. The analysis explores how the conditional nature of capital punishment aligns with or challenges the principle of legal certainty as a core value in Indonesian legal doctrine. The findings contribute to a deeper understanding of the coherence between penal policy and fundamental legal principles in the context of the new Criminal Code.Keywords: Conditional Death Penalty; Law Number 1 of 2023; Legal Certainty Principle